(untitled) (Medico Legal Update, 2019)
Background: Hypertension in elders is affected by physiological changes in the structure and cardiovascular functions. One alternative of non-pharmacological treatment for hypertension is the combination of foot massage and harp-flute (kecapi suling) music therapies, which can give a relaxing sensation in the blood pressure. Objective: This study aims to observe the effect of the combination of foot massage and kecapi suling music therapies against systolic and diastolic blood pressure. Method: This research uses the pre-experimental design (one group pretest-posttest design). The population was elders with hypertension in Werdha Hargo Dedali Nursing Home in Surabaya. Purposive sampling technique was used to obtain 14 respondents. The independent variables were foot massage and kecapi suling music therapies, whereas the dependent variable was the blood pressure reduction. The data were analyzed by using Paired-Samples T-Test with significance value ?0.05. Results: The study indicated that the combination of foot massage and kecapi suling music therapies affected systolic and diastolic blood pressure reduction in elders with hypertension. The systolic blood pressure average value in the pre-intervention was 154.64 mmHg, while the average value in the post-intervention was 138.86 mmHg. Diastolic blood pressure average value in the pre-intervention was 92.21 mmHg, while the average value in the post-intervention was 88.00 mmHg. Conclusion: There is an effect of the combination of foot massage and kecapi suling music therapies on decreasing blood pressure in elders with hypertension. The decrease in systolic blood pressure occurred in all respondents, while not all respondents experienced diastolic blood pressure declin